2014
DOI: 10.1542/peds.2013-2249
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electronic Medical Record–Enhanced Checklist and Electronic Dashboard to Decrease CLABSIs

Abstract: OBJECTIVES: We hypothesized that a checklist enhanced by the electronic medical record and a unit-wide dashboard would improve compliance with an evidence-based, pediatric-specific catheter care bundle and decrease central line-associated bloodstream infections (CLABSI). METHODS:We performed a cohort study with historical controls that included all patients with a central venous catheter in a 24-bed PICU in an academic children' s hospital. Postintervention CLABSI rates, compliance with bundle elements, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
107
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 30 publications
0
107
0
2
Order By: Relevance
“…[19][20][21] Third, the introduction of selfevaluation checklists, in general, can improve compliance with best clinical practice. 22 And finally, the HBB QIC progress boards placed in each unit provided a constant reminder to the staff of the quality improvement effort. Displaying data on implementation progress at each nursing station, in each delivery unit, allowed for constant review of and identification of potential problems in the implementation of the QIC, which has also been demonstrated in other quality improvement studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] Third, the introduction of selfevaluation checklists, in general, can improve compliance with best clinical practice. 22 And finally, the HBB QIC progress boards placed in each unit provided a constant reminder to the staff of the quality improvement effort. Displaying data on implementation progress at each nursing station, in each delivery unit, allowed for constant review of and identification of potential problems in the implementation of the QIC, which has also been demonstrated in other quality improvement studies.…”
Section: Discussionmentioning
confidence: 99%
“…Displaying data on implementation progress at each nursing station, in each delivery unit, allowed for constant review of and identification of potential problems in the implementation of the QIC, which has also been demonstrated in other quality improvement studies. 20,22 A cost-effectiveness evaluation of an HBB program in a hospital of Tanzania revealed that HBB is a low-cost intervention. 23 The HBB QIC as implemented in our study is also an affordable intervention.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23] Electronic health records have been used for electronic surveillance to automatically identify patients at risk 19 and to create checklists and dashboards to monitor unit-wide central line-associated bloodstream infections. 20 Computerized physician order entry and CDS have been shown to reduce catheter-associated urinary tract infections through electronic reminders and alerts that facilitate improved catheter management [21][22][23] and to reduce the risks of falls and pressure ulcers through electronic integration of protocols and risk assessments. 24,25 Beyond the direct effects on safety, EHRs can also indirectly reduce overall adverse event rates by enabling quality improvement initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we acknowledged the importance of checklist compliance as a validated and effective tool in the CLABSI reduction process. 17,25,26 Thus, 3 areas of vulnerability were targeted:…”
Section: Discussionmentioning
confidence: 99%